Evaluating the Bachelor of Education Program Based on the Context, Input, Process, and Product Model - Sankaran, Surendran; Saad, Norazlinda (Frontiers in Education, 2022)
The study aims to evaluate the Bachelor of Education (BEd) program based on the Context, Input, Process, and Product (CIPP) model. The CIPP paradigm was employed in this study, and data were collected utilizing a questionnaire, an interview guide, and related papers. A quantitative descriptive approach was used to analyze the data. The students, teachers, and top management employees of the polytechnic departments were evaluated. The study was analyzed using SPSS version 15. The descriptive statistics were used to make descriptions related to the respondents’ demographic backgrounds and the effectiveness of the BEd program. The prototype verification findings in the Glickman quadrant were used to assess the success of the learning program. According to the results, the execution of the teaching program at the polytechnic is successful considering the interdependence of CIPP. Lesson plan, semester teaching plans, curriculum, infrastructure, and facilities are the limits to the implementation of teaching at the polytechnic. The study concluded that it would be beneficial to the universities in Malaysia in the long-term effort to improve the quality of the program offered and increase the performance and wisdom of the trainers.